2012
DOI: 10.4236/ns.2012.42017
|View full text |Cite
|
Sign up to set email alerts
|

Feeding studies of radiation sterilization ready to eat foods on sprague dawley rats: <i>In vivo</i>

Abstract: Development of gamma irradiated high moisture traditional dishes derived from locally traditional récipe aimed for specific target groups as ready to eat foods for ensuring the safety, quality, and security purposes have been conducted. The formation of free radicals in the traditional foods induced by ionizing radiation is a part of toxicological studies on irradiated traditional foods was to provide local scientific data base on safety issues.The different foods such as steamed gold fish, spicy curry beef an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
2
3
0
2
Order By: Relevance
“…Therefore, the authors considered these changes to be episodic or adventitious ones due to the sensitive reactivity and response of hepatocytes to any toxicant or environmental pollutant since the liver is a target organ for contaminated food. This opinion is in agreement with other investigators (Maier et al,1993;Thayer ,1994;Kang et al,1998;WHO 1999;Hagiwara et al, 2005;Park et al, 2011;Irawati andSani, 2012 andKolawole, et al, 2015). Maier et al(1993) examined the histopathological inspection of liver, kidney, lung, spleen thymus and DNA analysis of bone marrow cells and nuclei of hepatocytes of rats in response to feeding irradiated wheat and found no significant association with the feeding process.…”
Section: Controlsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the authors considered these changes to be episodic or adventitious ones due to the sensitive reactivity and response of hepatocytes to any toxicant or environmental pollutant since the liver is a target organ for contaminated food. This opinion is in agreement with other investigators (Maier et al,1993;Thayer ,1994;Kang et al,1998;WHO 1999;Hagiwara et al, 2005;Park et al, 2011;Irawati andSani, 2012 andKolawole, et al, 2015). Maier et al(1993) examined the histopathological inspection of liver, kidney, lung, spleen thymus and DNA analysis of bone marrow cells and nuclei of hepatocytes of rats in response to feeding irradiated wheat and found no significant association with the feeding process.…”
Section: Controlsupporting
confidence: 92%
“…Park et al(2011) observed no microscopical alterations in liver and kidney of ICR mice fed 40 KGy-irradiated bulgogi. Irawati and Sani (2012) concluded that feeding of gamma irradiated food (45 kGy) in combination with packaging method of steamed gold fish, soy sauces beef and spicy curry beef to female rats, did not exhibit any pathological diagnosis nor clinical symptoms as compared to the un-irradiated food. Kolawole, et al (2015) recorded that consumption of γ-irradiated millet by Wistar rats at different doses (2-8KGy) caused no detectable histopathlogical lesions or any deformity in the cells of liver, kidney, heart, brain, spleen and lungs.…”
Section: Controlmentioning
confidence: 99%
“…This issue could probably be stated as scientific evidence that slow release of some nutritive food constituents which are trapped in the matrix might take place. Intensive studies on some irradiated ethnic RTE foods in vitro [ 7 , 8 ], animal feeding study in vivo [ 9 ], and food spectra using nanotechnology [ 20 , 21 ] show that antioxidant capacity tends to increase statistically, and could probably confirm the evidence. High quality, hygienic, and wholesome irradiated ethnic ready-to-eat foods could give a positive contribution [ 22 ] to improving the quality of life of the respondents.…”
Section: Discussionmentioning
confidence: 99%
“…In intensive in vitro and in vivo studies as a part of a risk assessment monitoring program, a high irradiation dose at 45 kGy of irradiated ethnic RTE showed promising results that such foods are safe and wholesome [ 7 , 8 , 9 ]. Due to some benefits of the process, high-dose irradiation can also potentially facilitate the availability of food for emergency rations as a source of nourishment and solace with a variability in menu, in which the food can be kept for long periods of time [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zaobserwowano, że w dużej mierze zależy ona oczywiście od dawki, ale również od rodzaju analizowanego produktu, jego przygotowania do radiacji, a także sposobu jego przechowywania i pakowania po zakończonym procesie. Zmiany oksydacyjne można ograniczyć poprzez zapakowanie napromieniowanych artykułów próżniowo przy użyciu odpowiednich materiałów oraz prowadząc proces w warunkach kriogenicznych [34].…”
Section: Charakterystyka Zmian Literaturaunclassified